2020
DOI: 10.1038/s41598-020-79210-4
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved RIXS experiment with pulse-by-pulse parallel readout data collection using X-ray free electron laser

Abstract: Time-resolved resonant inelastic X-ray scattering (RIXS) is one of the developing techniques enabled by the advent of X-ray free electron laser (FEL). It is important to evaluate how the FEL jitter, which is inherent in the self-amplified spontaneous emission process, influences the RIXS measurement. Here, we use a microchannel plate (MCP) based Timepix soft X-ray detector to conduct a time-resolved RIXS measurement at the Ti L3-edge on a charge-density-wave material TiSe2. The fast parallel Timepix readout an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Thus, the implementation of this future development together with iLGAD technology on silicon sensors would open the possibility of measuring single SXR photons with large-area hybrid detectors at high frame rates. Hybrid pixel detectors implemented with this future development are foreseen to meet the stringent requirements for conducting time-resolved resonant inelastic X-ray scattering for 3d transition metals with soft X-rays at synchrotron and free-electron laser facilities, which requires a high quantum efficiency, good signal-to-noise ratio, fast frame rates, large detection area, and fine pixel pitch, as outlined in [32,33]. Additionally, these detectors offer the advantage of expediting data acquisition in various techniques, such as R-SoXS and SXR ptychography within the water window or near the L-edges of 3d transition metals at synchrotrons.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the implementation of this future development together with iLGAD technology on silicon sensors would open the possibility of measuring single SXR photons with large-area hybrid detectors at high frame rates. Hybrid pixel detectors implemented with this future development are foreseen to meet the stringent requirements for conducting time-resolved resonant inelastic X-ray scattering for 3d transition metals with soft X-rays at synchrotron and free-electron laser facilities, which requires a high quantum efficiency, good signal-to-noise ratio, fast frame rates, large detection area, and fine pixel pitch, as outlined in [32,33]. Additionally, these detectors offer the advantage of expediting data acquisition in various techniques, such as R-SoXS and SXR ptychography within the water window or near the L-edges of 3d transition metals at synchrotrons.…”
Section: Discussionmentioning
confidence: 99%
“…In future, general, preferably analytical rules for the construction of a customized TDCM [23] or "compressor" [30] with hybrid, wavefront-corrected RZPs [26,27] on curved substrates [20] shall be derived. Matching the needs of high harmonic generators [32], laser-produced plasma sources [33] or free-electron lasers (FELs) [21,34] and addressing their characteristics with up-or down-chirps (Section 2), such an optimized instrument may open the door to advanced, even Fourier-limited applications such as time-resolved, ultra-fast resonant inelastic X-ray scattering (RIXS) spectroscopy [35,36]. Methods for the measurement of soft X-ray, (sub-)fs pulses and their parameters should be developed, too.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 So far bringing together these two fast-developing fields, RIXS and pump-probe spectroscopy at FEL, has been challenging, especially in the soft X-ray regime. Few time-resolved RIXS experiments have been performed for correlated materials, 38 with a focus on the study of the ultrafast dynamics of charge-order 39,40 as well as spin- 41,42 and orbital-excitations. 43 For instance, in CuGeO 3 recent time-resolved RIXS measurements revealed that the evolution of the magnetic degrees of freedom decouples from the other degrees of freedom on a 100 ps time scale.…”
Section: Future Perspectives: Time-resolved Rixs and High-energy Reso...mentioning
confidence: 99%
“…So far bringing together these two fast‐developing fields, RIXS and pump‐probe spectroscopy at FEL, has been challenging, especially in the soft X‐ray regime. Few time‐resolved RIXS experiments have been performed for correlated materials, 38 with a focus on the study of the ultrafast dynamics of charge‐order 39,40 as well as spin‐ 41,42 and orbital‐excitations 43 …”
Section: Future Perspectives: Time‐resolved Rixs and High‐energy Reso...mentioning
confidence: 99%